A qualitative study on learning organization as an essential action lowering skill mismatch effects - Yustina Erti Pravitasmara Dewi; Christantius Dwiatmadja; Lieli Suharti (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
Skill mismatch phenomenon has been discussed in various scientific journals as it is proven to lower productivity and weaken competitiveness. Understanding the skill mismatch effect on competitiveness leads to a new way of thinking about how to manage skill mismatch for the organization sustainability. Previous researches recognize the concept of organizational management in order to be able to compete by creating a learning organization environment. Adhering to the learning organization principles, individuals within the organization should increase their capacity and thus minimizing the negative effects caused by the skill mismatch effects. This study chooses hotel business as an observation unit as the hotel is such a storefront of tourism in Indonesia. The research was done in a descriptive-qualitative manner and used five-stars hotel in Indonesia. The results supported the previous researches on learning organization and training prior to working The findings indicated that in the process of organizational learning in the hospitality business, it was originally started with the involvement of the company or institutionalizing. The originality of this research is presented in the use of the 4i framework in organizational learning to evaluate the skill mismatch.
Keywords: D22; J24; O15; 650; skill mismatch; learning organization; training; mentoring; working; hotel; tourism